1995
DOI: 10.1093/oxfordjournals.eurheartj.a060793
|View full text |Cite
|
Sign up to set email alerts
|

Review of the long-term course of 52 patients with pulmonary atresia and ventricular septal defect

Abstract: This study reviews the long-term course of 52 patients with pulmonary atresia and ventricular septal defect seen in a single institution and followed for a mean period of 8.6 years (range 2 days to 20 years). Before the first operation, pulmonary blood supply was provided by ductus arteriosus supplying confluent pulmonary arteries in 26 patients (50%, group I), and was partially or entirely dependent on systemic collateral arteries in the other 26 patients (group II). The angiographic mean ratio of diameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The overall mortality rate observed in our series is comparable to that noted in previous studies. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The pRV/pLV is widely regarded as a surrogate measure of functional status after complete anatomic repair of this lesion. The pRV/pLV observed in our study is also comparable to that reported in other large series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall mortality rate observed in our series is comparable to that noted in previous studies. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The pRV/pLV is widely regarded as a surrogate measure of functional status after complete anatomic repair of this lesion. The pRV/pLV observed in our study is also comparable to that reported in other large series.…”
Section: Discussionmentioning
confidence: 99%
“…The pRV/pLV observed in our study is also comparable to that reported in other large series. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] We believe that this favorable pRV/pLV, particularly in patients who had extremely hypoplastic true pulmonary arteries with relatively few MAPCAs, is the result of the aggressive approach used to encourage growth of the true pulmonary arteries and aggressive recruitment of as many MAPCAs as possible in the repair, resulting in a larger effective pulmonary vasculature. In the univariate analysis we found that unifocalization of fewer than 3 MAPCAs in the repair was significantly associated with an increased likelihood of mortality and pRV/pLV Ͼ 0.55 (P Ͻ .05).…”
Section: Discussionmentioning
confidence: 99%
“…To date, several classification systems have been proposed. The Nakata Index 15 , 16 and McGoon ratio 17 , 18 have been used to evaluate the central/intrapericardial pulmonary arteries. The total neopulmonary artery index, a combined index for all major aortopulmonary collaterals and the central pulmonary artery, has been shown to correlate with postoperative right ventricle/left ventricle pressure ratio 9 .…”
Section: Discussionmentioning
confidence: 99%
“…The size of the branch pulmonary arteries is inversely proportional to the extent of MAPCAs and presence of a ductus arteriosus [102][103][104][105]. The angiographically determined Nakata index predicts good outcomes of complete repair of TOF with pulmonary artery hypoplasia if the index is greater than 100 mm 2 /body surface area (BSA) [106].…”
Section: Tof With Pulmonary Atresia And/or Extreme Pulmonary Hypoplasiamentioning
confidence: 99%